CONSTRUÇÃO E VALIDAÇÃO DE CARTILHA EDUCATIVA PARA PROMOÇÃO DA ADESÃO A ANTIDIABÉTICOS ORAIS - Gabriel Rios Roquini; Núbia Rafaela Nascimento Avelar; Thiago Rocha Santos; Marcela Regina Azevedo de Castro Oliveira; Nelson Miguel Galindo Neto; Maria Rui Miranda Grilo Correia de Sousa; Danilo Donizetti Trevisan (Cogitare Enfermagem, 2021)
Objective: to construct and validate an educational booklet to promote adherence to oral antidiabetic agents in people with Type 2 Diabetes Mellitus. Method: methodological study with construction and validation by a committee of 25 judges, conducted in 2020, in Minas Gerais, Brazil. Content, language, illustrations, layout, motivation, and culture were evaluated. The Content Validity Index was used, considering valid results equal to or greater than 0.80. Results: The booklet entitled “Planning to take medications in the treatment of type 2 Diabetes Mellitus. Let´s go?”, was composed of 24 pages with information on drug adherence, glycemic control, how to use the main oral antidiabetic agents, problems of nonadherence, and behavioral strategies for the effective taking of these medications. In content validation, CVI was 0.92. Conclusion: the booklet proved to be a valid educational material to be used to promote adherence to oral antidiabetic drugs.